Sensorial investigations a history of the senses in anthropology, psychology, and law - Howes, David 1957- (<<The>> Pennsylvania State University Press, 2023)
"Presents a history of the senses in the fields of anthropology, psychology, and law, identifying important shifts and key disciplinary concerns"--
Literaturverzeichnis Seite [245]-272
Keywords: Sinne; Wahrnehmung; Geschichte; Senses and sensation / History; Senses and sensation / Social aspects; Anthropology / History; Psychology / History; Anthropology; Psychology; Senses and sensation; History